Investigation of early-diverging land plant metabolism - Cannell, N (2021)
The terrestrialisation of embryophytes was preceded by, and precipitated, the evolution of diverse metabolic capabilities to aid growth and survival on land. A broad understanding of metabolism across all land plants is important for the discovery of novel metabolic enzymes and pathways which may be used commercially and to design metabolic engineering strategies for crop improvement. However, metabolic research has mainly focused on a small number of angiosperm crops and model plants. The research described in this thesis was carried out with the goal of correcting this knowledge bias, using bioinformatic and computational techniques to characterise metabolism, and its associated evolutionary processes, in early-diverging land plants.